2021
DOI: 10.3389/fonc.2021.674426
|View full text |Cite
|
Sign up to set email alerts
|

Rac1, A Potential Target for Tumor Therapy

Abstract: RAS-related C3 botulinum toxin substrate 1 (Rac.1) is one of the important members of Rho GTPases. It is well known that Rac1 is a cytoskeleton regulation protein that regulates cell adhesion, morphology, and movement. Rac1 is highly expressed in different types of tumors, which is related to poor prognosis. Studies have shown that Rac1 not only participates in the tumor cell cycle, apoptosis, proliferation, invasion, migration and angiogenesis, but also participates in the regulation of tumor stem cell, thus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 204 publications
(206 reference statements)
3
47
0
1
Order By: Relevance
“…Guanine nucleotide-binding proteins (or G-proteins) regulate multiple cellular processes and are observed to be hyper-activated in many human cancers 1 . While a few activating point mutations of Ras-related C3 botulinum toxin substrate 1 (RAC1), a member of the RHO-GTPases family of G-proteins, have been identified in malignancies such as melanoma, breast, and head and neck cancers 2 – 5 , the mechanisms behind the overall over-activation of GTPases in cancer has not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guanine nucleotide-binding proteins (or G-proteins) regulate multiple cellular processes and are observed to be hyper-activated in many human cancers 1 . While a few activating point mutations of Ras-related C3 botulinum toxin substrate 1 (RAC1), a member of the RHO-GTPases family of G-proteins, have been identified in malignancies such as melanoma, breast, and head and neck cancers 2 – 5 , the mechanisms behind the overall over-activation of GTPases in cancer has not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…In the active, GTP (guanosine triphosphate)-bound, form RAC1 interacts with downstream effectors triggering activation of multiple signaling pathways ultimately resulting in regulation of cell motility, invasion, and progression through the cell cycle 2 6 . On the contrary, GDP-bound RAC1 is inactive.…”
Section: Introductionmentioning
confidence: 99%
“…Rac1 belongs to the Rho family of GTPases that play key roles in cytoskeleton reorganization, cell polarity, and cell migration [59]. Like all GTPases, Rac1 is active in its GTP-bound form and inactive in its GDP-bound form [60].…”
Section: Ras-related C3 Botulinum Toxin Substrate 1 (Rac1) Mediated S...mentioning
confidence: 99%
“…Comparative proteomic analysis of head and neck squamous carcinoma cell lines FaDu and SCC25 with radiation-resistant cell lines FaDu-RR and SCC25-RR showed that Ras-related C3 botulinum toxin substrate 1 (Rac1) could be used as a new therapeutic target ( 52 ). Rac1 is a cytoskeleton involved in cell adhension, morphology, and movement; overexpression of Rac1 is associated with unfavorable survival in different type of cancer ( 53 ).…”
Section: Radiosensitivity Biomarkers In Cancersmentioning
confidence: 99%